Extraction and Determination of Bioactive Compounds from Premna Foetida Leaves - Muhammad Habib Adnin,; Muhammad Faris Daniel Azman,; Rahayu Ahmad,; Ehwan Ngadi (Universiti Sains Islam Malaysia, 2024)
Junior Researcher International Conference (iJURECON) Kolej Genius Insan (KGI) 17 dan 18 November 2020 Pages : 72-76